Growth Enhancement of Arabidopsis (Arabidopsis thaliana) and Onion (Allium cepa) With Inoculation of Three Newly Identified Mineral-Solubilizing Fungi in the Genus Aspergillus Section Nigri - Khuna, Surapong; Suwannarach, Nakarin; Kumla, Jaturong; Frisvad, Jens Christian; Matsui, Kenji; Nuangmek, Wipornpan; Lumyong, Saisamorn (Frontiers in Microbiology, 2021)
Some soil fungi play an important role in supplying elements to plants by the solubilizing of insoluble minerals in the soil. The present study was conducted to isolate the mineral-solubilizing fungi from rhizosphere soil in some agricultural areas in northern Thailand. Seven fungal strains were obtained and identified using a polyphasic taxonomic approach with multilocus phylogenetic and phenotypic (morphology and extrolite profile) analyses. All obtained fungal strains were newly identified in the genus Aspergillus section Nigri, Aspergillus chiangmaiensis (SDBR-CMUI4 and SDBR-CMU15), Aspergillus pseudopiperis (SDBR-CMUI1 and SDBR-CMUI7), and Aspergillus pseudotubingensis (SDBR-CMUO2, SDBR-CMUO8, and SDBR-CMU20). All fungal strains were able to solubilize the insoluble mineral form of calcium, copper, cobalt, iron, manganese, magnesium, zinc, phosphorus, feldspar, and kaolin in the agar plate assay. Consequently, the highest phosphate solubilization strains (SDBR-CMUI1, SDBR-CMUI4, and SDBR-CMUO2) of each fungal species were selected for evaluation of their plant growth enhancement ability on Arabidopsis and onion in laboratory and greenhouse experiments, respectively. Plant disease symptoms were not found in any treatment of fungal inoculation and control. All selected fungal strains significantly increased the leaf number, leaf length, dried biomass of shoot and root, chlorophyll content, and cellular inorganic phosphate content in both Arabidopsis and onion plants under supplementation with insoluble mineral phosphate. Additionally, the inoculation of selected fungal strains also improved the yield and quercetin content of onion bulb. Thus, the selected strains reveal the potential in plant growth promotion agents that can be applied as a biofertilizer in the future.